THE PERSONALITY OF APRIL WHEELER IN SAM MENDES'S REVOLUTIONARY ROAD (2009) MOVIE:A PSYCHOANALYTIC APPROACH - IMRO'AH, IMRO'AH (2011)
The research is proposed to analyze the personality of April in a film with the title Revolutionary Road with a Psychoanalytic Approach. There are two objectives: the first is to analyze the film in term of structural element, and the second is to analyze the film based on Psychoanalytic Approach. The type of the research is qualitative. The primary data source that used by the writer is Revolutionary Road movie and the script which written by Justin Haythe. Movie script was taken from a website. The secondary data are taken from other sources which related to this movie such as biography of the author and the other relevant information. The method of collecting data is library research whereas the technique for analyzing is descriptive analysis. In this study, the writer draws two conclusions as follows: first, in Revolutionary Road, through the kinds of the structural elements, it can be seen that the structural elements of the film has contribution in creating the film. It also supports each other because the theme, character and characterization, plot, mise_en_scene, sound, editing comprehensively build unified structure and give contribution to the total meaning of work. Secondly, Revolutionary Road is a story charged with ambition and emotion, in which the integrity of being human meets a terrifying test. Sam Mendes in Revolutionary Road movie described the doubt in the personality of major character. She is faced with conflict between id and superego that influence her decision to get meaningful life. Finally, her id dominated the ego than superego.